European Journal of Applied Linguistics (De Gruyter Mouton, 2013)
The European Journal of Applied Linguistics focuses on the particular concerns of applied linguistics in European contexts, both by addressing problems that are typically relevant for the linguistic situation in Europe, and by examining topics broached by or discussed in European applied linguistics in particular. The journal is part of the joint activities of the European AILA affiliates.